2014
DOI: 10.1371/journal.pone.0095530
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitory, Bactericidal, and Morphostructural Effects of Dehydrocostus Lactone from Magnolia sieboldii Leaves on Antibiotic-Susceptible and -Resistant Strains of Helicobacter pylori

Abstract: Helicobacter pylori is associated with various diseases of the upper gastrointestinal tract, such as gastric inflammation and duodenal and gastric ulcers. The aim of the study was to assess anti-H. pylori effects of the sesquiterpene lactone dehydrocostus lactone (DCL) from Magnolia sieboldii leaves, compared to commercial pure DCL, two previously known sesquiterpene lactones (costunolide and parthenolide), (–)-epigallocatechin gallate, and four antibiotics. The antibacterial activity of natural DCL toward ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
6
27
0
Order By: Relevance
“…DHE is a naturally occurring sesquiterpene lactone reported to have many biological effects, including anticancer, bactericidal and antioxidative stress properties. 9,14,15 However, there has been no report examining the effects of DHE on osteoclasts. In this study, we investigated its effects on RANKL-induced osteoclast formation and function, and determined the underlying mechanism in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…DHE is a naturally occurring sesquiterpene lactone reported to have many biological effects, including anticancer, bactericidal and antioxidative stress properties. 9,14,15 However, there has been no report examining the effects of DHE on osteoclasts. In this study, we investigated its effects on RANKL-induced osteoclast formation and function, and determined the underlying mechanism in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In a set of eleven studies [45][46][47][48][49][50][51][52][53][54][55] determining an activity and morphological effect of plant extracts and plant-derived compounds on H. pylori, four of them reported a bacteriostatic activity [45][46][47][48] and six indicated a bactericidal effect [49][50][51][52][53][54] of the tested compounds. In one case, the use of this classification was avoided [55].…”
Section: Plant Extracts and Plant-derived Compoundsmentioning
confidence: 99%
“…The six studies indicated the bactericidal effect of the tested compounds on H. pylori [49][50][51][52][53][54]. A capacity to completely inhibit growth was only proven in half of them [49,51,52], which was achieved in a range of 18 h [49] to 72 h [51] with MICs. A relationship between the decrease in viability and number of spherical forms was particularly well illustrated in the Lee et al article [51].…”
Section: Plant Extracts and Plant-derived Compoundsmentioning
confidence: 99%
“…provinces, because of its medicinal and ornamental values. It is an important Chinese traditional medicinal plant that is used frequently as stomachic, analgesic and anthelmintic in folk medicines [1], due to its pharmacological activities, such as antiinflammatory [2], anti-tumor [3], and anti-bacterial activity [4]. Phytochemical and pharmacological studies have illustrated that Magnoliaceae are full of many kinds of biologically active substances such as magnolol, honokiol, magnoshinin and magnosalin [1,5], in addition, the essential oil of Magnoliaceae has been researched [6,7].…”
Section: Introductionmentioning
confidence: 99%